1999
DOI: 10.1002/(sici)1097-4628(19990923)73:13<2779::aid-app27>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reaction of stannic oxide in silicone rubber at 300�C

Abstract: The thermal stability of high-temperature vulcanized silicone rubber with stannic oxide as a heat stabilizer was investigated by heat aging at 300°C ϫ 24 h in air. It was discovered that Sn ϩ4 is reduced to Sn 0 during vulcanization and during heat aging in air by X-ray photoelectron spectroscopy (XPS). EXPERIMENTALXPS analyses were carried out in a Perkin-Elmer PHI-1600 X-ray photoelectron spectrometer in a vacuum of 10 Ϫ8 Pa. For each specimen, a survey spectrum was recorded, together with high-resolution sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Many investigations have shown that rare earth compounds have specific functions in the production and use of rubber [8][9][10], thermal resistance [11], antifatigue [12], strengthening action [13][14][15][16], and antioxidation [17]. Metal oxides can be used as heat-resistant additions [18][19][20]. A notable rare earth chemical is CeO2.…”
Section: -Introductionmentioning
confidence: 99%
“…Many investigations have shown that rare earth compounds have specific functions in the production and use of rubber [8][9][10], thermal resistance [11], antifatigue [12], strengthening action [13][14][15][16], and antioxidation [17]. Metal oxides can be used as heat-resistant additions [18][19][20]. A notable rare earth chemical is CeO2.…”
Section: -Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] As one of the few elastomers used in extreme conditions, FSR needs to be modified to enhance its heat resistance, enabling to serve for new technology. 14,15 However, FSR is even less heat stable than SR because FSR is more susceptible to siloxane bond cleavage and oxidative degradation. As is well known, the silicone rubbers (SR) tend to deteriorate at temperature above 200 8C for extended periods of time, because of two mechanisms: (1) the degradation or reversion of the main chain to generate low molecular weight cyclosiloxanes; (2) the oxidation scission of the side groups.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the silicone rubbers (SR) tend to deteriorate at temperature above 200 8C for extended periods of time, because of two mechanisms: (1) the degradation or reversion of the main chain to generate low molecular weight cyclosiloxanes; (2) the oxidation scission of the side groups. 14,15 However, FSR is even less heat stable than SR because FSR is more susceptible to siloxane bond cleavage and oxidative degradation. [16][17][18] It has been common practice to add metal oxides (Fe 2 O 3 , CeO 2 , SnO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] To date, several materials have already been blended with MESRs. Metal oxides 15 and antioxidants 16 can improve the thermal stability. However, poor compatibility usually significantly reduces the mechanical properties of materials.…”
Section: Introductionmentioning
confidence: 99%